ROLE OF THE STATE AND CIVIL SOCIETY IN HUMAN RIGHTS PROMOTING: SOCIOLOGICAL CONCEPT - PODOROZHNA, T. (Ehrlich's Journal, 2023)
The article is devoted to the problems of human rights promotion by institutions of the civil society and the state. The mentioned problems are considered in the light of sociological concepts by Ehrlich. Attention is drawn to the fact that modern state and legislation-making processes in Ukraine, despite their complexity and contradictions, are impossible to be imagined beyond the ideas and ideals of democracy and the rule of law, strengthening and ensuring of the rights and freedoms of a person. It is noted that the law is directly linked to empowering of citizens with unalienable, recognized from the birth rights relating to freedom, equality and independence. Studying of the law only as a written, static phenomenon restricted by statute substantially narrows its scope. Written law contained in the statute, includes general rules, which are not always able to respond flexibly to changes in socio-economic and political life of society. It is grounded that positive law itself is not able to meet all the needs of society and through total indoctrination is unable to comprehend social reality. Therefore, the law cannot be fully and thoroughly investigated out of touch with society as a social system, out of social connections existing in a society. On these grounds it is concluded that the statute should be public law, and its main purpose – is the protection of freedom because freedom is the basis of human life order. The effectiveness of the state depends on how it is able to accumulate common interests and implement them in its policy.